DIGITAL LITERACY AND UTILIZATION OF COMMUNITY READING CORNER - Siti Nurjanah; Anisa Fitriani; Anisa Fitri; Eka Apriani Putri; Iklima Nurul Fudhlah; Isnaini Nurhayati; Muhammad Ridwan; Meida Widianti; Nur Asti Maulida; Putri Mentari; Riska Damyanti; Sofi Safiqa Raihani; Rasmitadila Rasmitadila (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
The literacy program is aimed at villagers (4 target residents) through reading activities through enrichment of knowledge, skills and personality to add insight in accordance with the field of work of villagers in order to improve their welfare. The specification of the Village Literacy Program Assistance (PROLISA) is a literacy corner that functions as a community learning center that has a certain non-formal learning curriculum. Then for the topics covered in the Literacy Corner, it is intended to broaden people's insight, knowledge, attitudes and skills that are useful for improving their welfare. And the activities that we carry out will be directed at getting changes in attitudes and behavior by facilitating literacy books on motivation, general knowledge, and crafts. The holding of digital literacy socialization explains how to use digital tools properly and correctly so that people can use these tools as capital for online businesses.